1997
DOI: 10.1177/070674379704200509
|View full text |Cite
|
Sign up to set email alerts
|

Choking Incidents among Psychiatric Patients: Retrospective Analysis of Thirty-one Cases from the West Bologna Psychiatric Wards

Abstract: Various simple, effective preventive measures emerge from the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
0
46
1
Order By: Relevance
“…Table 3 shows how each clinical sign was distributed among subjects in both groups. study and other published papers are due both to the methods for evaluating swallowing and to observing carefully the relationship between food consistency and clinical signs [5][6][7][8][9][10][11]19,21,[23][24][25] . Therefore, while one of those studies found changes in 30% of subjects, and another found changes in 90% of subjects, we encountered no significant effect of neuroleptic drugs on swallowing 7,11 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 shows how each clinical sign was distributed among subjects in both groups. study and other published papers are due both to the methods for evaluating swallowing and to observing carefully the relationship between food consistency and clinical signs [5][6][7][8][9][10][11]19,21,[23][24][25] . Therefore, while one of those studies found changes in 30% of subjects, and another found changes in 90% of subjects, we encountered no significant effect of neuroleptic drugs on swallowing 7,11 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies applied specific swallowing evaluation methods in subjects taking neuroleptics and found disorders in a significant number of their sample 7,11 . These studies, however, were not controlled and patients belonged to several age groups, including elderly subject; the latter have specific physical features and systemic diseases that may lead to dysphagia [8][9][10] . Furthermore, the authors did not describe the clinical signs in those patients, and used only a watery consistency without informing the volume 7,11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations